Desinfektan Nabati Untuk Menurunkan Jumlah Kuman Udara Dan Lantai Di Ruang Laboratorium - Sri Muryani (POLTEKKES KEMENKES YOGYAKARTA, 2016)
Based on the result of air quality examination at environmental health department laboratory conducted by student in 2014, it was obtained the air germs 870 CFU/m3 while the standard of air germs in laboratory is 200-500 CFU/m3. It shows that it exceeds the standard quality of air. Air quality that is not qualified may cause health problems such as flu, cough, respiratory infections, hypersensitivity (asthma, allergies) and even one bacterium Legionella sp, causes Legionnnaire disease. One of the efforts made to reduce air germs and floor germs is performing disinfection with garlic extract. Chemical disinfectants are replaced with plant-based ingredients which are easily degraded by bacteria in the environment and safe for human. Garlic contains volatile oil which is anti-bacterial and antiseptic as well allicin and aliin. All of it makes garlic has many health benefits. It was also said by Louis Priest in 1985 and even found that garlic can kill bacteria. The purpose of this study was to determine garlic extract that can be used as an alternative disinfectant to kill air and floor germs. The method used is experimental with pre-post group design . This study measured the number of floor and air germs before and after disinfection, then disinfection is performed by fumigation with concentrations of 15 % , 20 % and 25 % of garlic extract and then exposed for 2 hours and post- test examination was then conducted. The data were analyzed using multivariate SPSS program one way anava with the significance level of 95 %, p = < 0.000 . After analyzing the data, it can be seen that the results for the number of floor germ was p= < 0 ,000, and the number of air germ was p = < 0.000 , it means that there was an influence of plant-based disinfectant to reduce floors and air germs. It can be concluded that plant-based disinfectant with concentration of 15 % can reduce 33.00 CFU/m2 floor germs and 733 CFU/m3 air germs, and the concentration of 20 % reduce 21,40 CFU/m2 (52.54%) of floor germs and 484.33 CFU/m3 (54,13 %) of air germs and the concentration of 25 % can lower 42.12 CFU/m2 ( 66.99 % ) of germs floor and 1,173 CFU/m3 (68.11 %) air germs. From various concentrations of garlic extract disinfectant, the 25 % concentration of garlic extract is the most effective plant-based disinfectant for floor and air germs.